Inventory optimization of perishable items using a shelf life-based heuristic approach - Nadiah Khairunnisa; Nur Mayke Eka Normasari (OPSI, 2025)
This study develops a practical inventory control model for perishable pharmaceutical products by addressing the common limitation of traditional inventory methods that often overlook product shelf life or require complex optimization procedures. The proposed model enhances practicality by integrating shelf-life considerations into the (R, nQ) heuristic approach, allowing order quantities and reorder points to be determined through a simple and easily implementable procedure. This approach is further combined with a multi-criteria ABC classification that incorporates annual demand, lead time, and unit cost, enabling more informed prioritization of inventory items. The model was applied to 243 pharmaceutical products in a health department. The results show that incorporating shelf-life constraints reduced the inventory value of items exceeding their usable period by 45% and generated an overall 2% decrease in total inventory value. These findings demonstrate the model’s ability to minimize waste due to expiration while maintaining operational feasibility. By offering a straightforward and shelf-life–integrated decision rule, the model provides a more practical alternative to existing inventory methods, especially in healthcare settings with limited analytical resources.